The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5433/1679-0359.2015v36n3p1725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgical castration, immunocastration and homeopathy on the performance, carcass characteristics and behaviour of feedlot-finished crossbred bulls

Abstract: Effects of surgical castration, immunocastration and homeopathy on the performance, carcass characteristics and behaviour of feedlotfinished crossbred bullsEfeitos da castração cirúrgica, imunocastração e homeopatia sobre o desempenho, características de carcaça e comportamento de bovinos machos cruzados terminados em confinamento AbstractThe aim of this study was to evaluate total weight gain, carcass yield, rib-eye area, marbling, subcutaneous fat thickness, frequencies of mounting, excitement, dominance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…The different rib eye areas between treatments could be attributed to the effect of testosterone in bulls (Lee, Henricks, Skelley, & Grimes, ). De Freitas et al () suggested that these differences are possibly because testosterone promotes muscular development throughout bull life due to increased nitrogen retention (Galbraith, Demspter, & Miller, ). Prior, Smith, Schanbacher, and Mersmann () suggested that testosterone has an inhibitory effect on lipogenic enzyme activities present in the adipose tissue, inducing higher basal lipolytic rates.…”
Section: Resultsmentioning
confidence: 99%
“…The different rib eye areas between treatments could be attributed to the effect of testosterone in bulls (Lee, Henricks, Skelley, & Grimes, ). De Freitas et al () suggested that these differences are possibly because testosterone promotes muscular development throughout bull life due to increased nitrogen retention (Galbraith, Demspter, & Miller, ). Prior, Smith, Schanbacher, and Mersmann () suggested that testosterone has an inhibitory effect on lipogenic enzyme activities present in the adipose tissue, inducing higher basal lipolytic rates.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported a decrease in the frequency of behaviours such as mounting, threats, and head butts in immunocastrated males when compared with uncastrated males (Huxsoll et al 1998, Marti et al 2015, Freitas et al 2015. These differences may be due to the effect that immunocastration has on serum testosterone levels where the synthetic GNRH contained in the vaccine (Bopriva™) stimulates the production of antibodies by the animal immune system.…”
Section: Discussionmentioning
confidence: 77%
“…The antibodies block the GNRH receptors located in the hypophysis and therefore inhibit the release of the hormones FSH and LH that are responsible for stimulating the production of testosterone in the gonads, and as a result testosterone levels in bloodstream will be reduced (Herbert and Trig 2005). Freitas et al (2015) showed that there is a positive correlation among testosterone levels and the frequency of mounts and agonist behaviour, and they believe that high testosterone levels stimulate a homosexual behaviour. Therefore, when testosterone levels fall, also physical activity will be decreased and so sexual and aggressive behaviour occurrence will be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Sua utilização justifica-se pelo fato de não infringir dor aguda e desconforto aos bovinos, quando em relação à castração cirúrgica (Marti et al, 2015). Alguns estudos têm sido desenvolvidos visando avaliar os efeitos dos métodos de castração, castração imunológica ou cirúrgica, sobre características de carcaça e carne em bovinos de corte (Amataiakul-Chantler et al, 2013;Miguel et al, 2014;Freitas et al, 2015). Todavia, nesses estudos, os dois métodos de castrações foram aplicados em períodos imediatamente anteriores à fase de engorda, logo em bovinos com idade pós-púbere.…”
Section: Introductionunclassified